Perancangan Ikat Pinggang Pendeteksi Halangan untuk Tunanetra dengan Metode Half Cylinder Berbasis Single Board Microcontroller Bertenaga Panel Surya - Adlan Bagus Pradana; Muhammad Arief Wibowo; Astri Sumartopo; Jimmy Trio Putra (Jurnal Arus Elektro Indonesia, 2021)
On this earth, not a few humans have physical deficiencies in the form of five imperfect senses, one of which is blind people. Blind people are someone who is unable to see well because their visual system is impaired due to heredity, accidents, or other factors. In their activities, blind people need assistive devices in the form of a guidepost to find out the appropriate and safe direction of the road. However, it is not common for blind people who still have difficulty walking using manual walking sticks which are considered to have a low level of accuracy. This is then used as the main idea of ​​the research which aims to create an automatic guide in the form of an obstacle detection belt for the visually impaired using a half cylinder method based on a single board microcontroller using solar panel powered. This tool is an innovation of a manual walking stick developed by utilizing the HC-SR04 ultrasonic sensor as an obstacle detector and the Arduino nano control system by applying the half cylinder method to the area of ​​catching the reflected obstruction waves. The reflected waves captured by the HC-SR04 ultrasonic sensor are then converted into distance units to determine the output of the DC motor and buzzer. Keywords — blind people, walking stick, obstacle detection belt.